Case Study: Awarding Education of Fluids Restriction Management on Impaired Kidney Perfusion for Improving Self-Efficacy of Patients and Families - Estin Yuliastuti; Suhartini Suhartini (International Journal of Nursing and Health Services (IJNHS), 2018)
Non-adherence to fluid restriction on impaired kidney perfusion problems will lead to chronic excess fluid and increase the risk of other disease complications. Self-efficacy is an important component of achieving goals. Fluids restriction management education in the impaired kidney perfusion problems is the main thing that required to improving self-efficacy of patients and families. The purpose of this case study is to examine self-efficacy of patients with impaired kidney perfusion before and after fluids restriction management education in patients and families. Cases study was performed on two patients with impaired kidney perfusion. Fluid restriction management education on patients and families are given to improve self-efficacy. Self-efficacy scores on Mr. Y before the education are 105 and 112 after education, while the self-efficacy scores on Mr. E before the education are 111 and 113 after education. Furthermore, both patients stated to be more assured on adherence to fluid restriction management for impaired kidney perfusion. Education of fluid restriction management in patients and families with impaired kidney perfusion can improve self-efficacy in patients. Nurses can educate the patients and families by multiplying methods and instructional media.